Current vaccination status and safety of children with peripheral neuroblastoma in the real-world - Shen, Heping; Xu, Yuyang; Zhan, Yuxuan; Liu, Yan; Zhang, Xuechao; Li, Mingyan; Ji, Chai (Frontiers in Immunology, 2024)
Background peripheral neuroblastic tumors (pNT) have high incidence and mortality, and infants are prone to various infectious diseases. The purpose of this study is to understand the immunization status of children with pNT in the real-world and the incidence of adverse reactions after vaccination, and to evaluate the feasibility of vaccination and the influencing factors of vaccination. Methods Children with pNT treated in the Children’s Hospital Affiliated to Zhejiang University from January 1, 2011 to December 1, 2021 were included. By referring to medical records, the vaccination history of the national immunization program (NIP) vaccines and the occurrence of adverse events following immunization(AEFI), current status and safety of immunization in children with pNT in the real-world were analyzed. Results Among 784 children with pNT, 394 were able to obtain the history of vaccination. The overall vaccination rate of NIP vaccines was 71.49% before chemotherapy and 37.67% after chemotherapy, and the recovery time of vaccination after treatment was 16.00 (6.00,24.00) months. Age, time of tumor diagnosis and disease classification were significantly correlated with vaccination. AEFI reported an incidence of 0.23‰. Conclusion The vaccination rate of children with pNT is generally low, especially the vaccination rate after chemotherapy. The vaccination safety is good, children should be encouraged to immunize.